Current Understanding of the Glial Response to Disorders of the Aging CNS - Cicchetti, Francesca; Barker, Roger A. (Frontiers in Pharmacology, 2012)
In this special issue of Frontiers in Neuropharmacology, we have asked leading experts to comment and review the evidence that inflammatory cells play a leading role in the pathological processes underlying neurodegenerative disorders. We now seek to draw these various observations together into a conclusion, with the hope that this will inform further work in this area and lead to the identification of new therapeutic targets that will have a disease modifying effect.